Dinosaur boy - Oakes, Cory Putman (Sourcebooks Jabberwocky, 2015)
Sprouting a tail and spikes over the summer before fifth grade, Sawyer, a boy with the dinosaur gene, is bullied in school, but when his tormentors begin to disappear, it is up to Sawyer, his best friend Elliot, and a mysterious new girl to rescue them from a galactically horrible fate.